Expression of Transforming Growth Factor–Beta (TGF-β) on Regulatory T (Treg) Cell from Skin Lesion of Leprosy’s Patient - Kristina Sihaloho; Afif Nurul Hidayati; Indropo Agusni (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Clinical manifestations of leprosy depends on host’s immunity. Regulatory T (Treg) cells are known as CD4+CD25+FOXP3+ have roles in immune respons to maintain homeostasis. Transforming growth factor (TGF)-β are one of cytokine that is secreted by Treg cells. Treg cells are thought as unresponsiveness T cells (anergy) to Mycobacterium leprae and caused disease’s progression to lepromatosa. Purpose: To evaluate expression of TGF-β on Treg cells from patient leprosy’s skin lession. Methods: Design of study was cross-sectional, descriptive observation involving 18 leprosy patients who visited the Leprosy Division, Dermatology and Venereology Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya. Biopsy from skin lession were performed then continued with histopathological examination. The type of leprosy was determined by clinical and histopathological examinations. Expression of TGF-β on Treg cell were performed by double staining immunohistochemistry in Biomoleculer and Pathology and Anatomy Laboratory at Brawijaya University, Malang. Result: Numbers of mid-borderline type (BB) leprosy’s patients were 2 (11,1%),  9 (50%) patients with borderline lepromatosa (BL) type, and 7 (38,5%) patients with Lepromatosa (LL) type. Mean expression of TGF-β on Treg cells from skin lession’s leprosy on BB type was 12 ± 2,12 cells/field of view, on BL type was 16 ± 3,64 cells/fields of view and on LL type was  22± 3,69 cells/field of view. Conclusion: Expression of TGF-β on Treg cells are increasing on skin lession’s leprosy patients might as prognostic indicator of severity of leprosy (lepromatosa type).                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                                          Key words: immunohistochemistry, leprosy, Morbus Hansen, regulatory T cell, TGF-β.